Servo-System Simulation; Mechanical Engineering, Automation and Control Systems (MEACS) - Reshetnikova G. N.; Khabibulina N. Yu. Nadezhda Yurievna; Kotsubinskiy V. P. Vladislav Petrovich; Polonskaya M. S. Marina Sergeevna (2015, 2015)
Title screen